2018
DOI: 10.1111/ffe.12810
|View full text |Cite
|
Sign up to set email alerts
|

Influence of solidification defects on the fatigue behaviour of heavy‐section silicon solution–strengthened ferritic ductile cast irons

Abstract: Mechanical and fatigue properties of heavy section solution–strengthened ferritic ductile iron (SSF‐DI) castings have been examined in this contribution. Amounts of silicon varying from 3.2 to 3.55 wt% have been used. The effect of antimony on counteracting the formation of chunky graphite has been evaluated. In order to estimate the influence of solidification defects (microshrinkage porosities or degenerated graphite particles) on the fatigue strength of the investigated materials, scanning electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Considering the fatigue crack propagation in DCIs and the influence of the matrix microstructure, some different damaging mechanisms connected to the graphite nodules presence were identified: graphite elements—matrix debonding, “onion‐like” mechanism (where a crack initiates and propagates at the interface between the nodule core obtained directly from the melt and characterized by a lower resistance and the nodule shell, obtained during the cooling process and due to the carbon atoms solid diffusion) and the nodule disaggregation, where the crack propagates through the nodule. According to the experimental results, the importance of the damaging mechanisms is not influenced by the applied ΔK, but it depends on the matrix microstructure. For example, focusing on the ferritic DCI, the “onion‐like” mechanism seems to be the most frequent one.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the fatigue crack propagation in DCIs and the influence of the matrix microstructure, some different damaging mechanisms connected to the graphite nodules presence were identified: graphite elements—matrix debonding, “onion‐like” mechanism (where a crack initiates and propagates at the interface between the nodule core obtained directly from the melt and characterized by a lower resistance and the nodule shell, obtained during the cooling process and due to the carbon atoms solid diffusion) and the nodule disaggregation, where the crack propagates through the nodule. According to the experimental results, the importance of the damaging mechanisms is not influenced by the applied ΔK, but it depends on the matrix microstructure. For example, focusing on the ferritic DCI, the “onion‐like” mechanism seems to be the most frequent one.…”
Section: Introductionmentioning
confidence: 99%
“…The TM method consists in an evaluation of the point with a given probability (and confidence limit) at each testing stress level, and then the P ‐ S ‐ N regression is made considering these points. The accurate P ‐ S ‐ N results can be obtained by the TM method only when the sample size is large enough . More importantly, P ‐ S ‐ N curves will be even more costly and more time‐consuming when facing the situation of large‐scatter data, because fatigue failure is sensitive to many factors such as microstructure and defects of materials as well as specimen surface quality .…”
Section: Introductionmentioning
confidence: 99%
“…The accurate P-S-N results can be obtained by the TM method only when the sample size is large enough. [8][9][10] More importantly, P-S-N curves will be even more costly and more time-consuming when facing the situation of large-Nomenclature: A, B, m, fitting parameters of P-S-N curves; C, confidence level; CV i , coefficient of variation of the logarithmic fatigue life at the ith stress level; ESS, explained sum of squares; EQ, new method for determining P-S-N curves in terms of equivalent fatigue lives; F (), cumulative distribution functions; I, number of testing stress levels; ISO, International Standard Organisation; J i , number of all the experimental life data at the ith stress level; k, one-sided tolerance limit factor; l i , number of the experimental life data used for P-S-N curve fitting at the ith stress level; N, lgN, fatigue lives, and logarithmic fatigue lives; N i,j , fatigue life of the specimen j at the ith stress level; N ω , lgN ω , fatigue lives, and logarithmic fatigue lives of the mixed sample at the baseline stress level; lgN C,R,i , logarithmic fatigue with the confidence level C and survival level R; lg(N C,R,i ) f , lg(N C,R,i ) a , fitted logarithmic fatigue lives, and accurate logarithmic fatigue lives with the confidence level C and survival level R at the ith stress level; Φ, cumulative distribution function of the standard normal distribution; μ i , μ Base , median logarithmic fatigue life at the ith stress level, and at the baseline stress level; R, survival level; RSS, residual sum of squares; S i , stress level with the order of i; TM, traditional method for determining P-S-N curves; σ i , standard deviation of the logarithmic fatigue life at the ith stress level; t, testing time; U, unified coefficient of variation; v, sample size of the mixed sample; w, fatigue life order for the mixed sample; χ, precision level scatter data, [11][12][13] because fatigue failure is sensitive to many factors such as microstructure and defects of materials as well as specimen surface quality. [14][15][16] Therefore, it is of great necessity to propose a new method for determining P-S-N curves, which can save testing time and improve testing efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Although CHG has been considered in many studies, no generally accepted theory for its formation has been found yet. What is known is its detrimental effect on the mechanical properties, with particular reference to the ultimate tensile strength and ductility; but CHG seems also to affect the crack propagation stage during fatigue loadings [13][14][15]. While in the case of spheroidal graphite particles, decohesion between the nodules and the metal matrix happens, the crack propagates easily through the chunky graphite areas.…”
Section: Introductionmentioning
confidence: 99%
“…While a great effort was spent in the past in order to characterize the traditional ductile irons with ferritic and/or pearlitic matrices, limited data is available in technical papers regarding the new generation ductile irons (SSF-DI) [14,17,24]. Furthermore, only the mechanical properties versus thickness correlation is found, the main drawback of which is that equal thicknesses do not mean necessary equal microstructure and thus mechanical properties.…”
Section: Introductionmentioning
confidence: 99%